Relationship Between Land Tenure Practices And Food Security At Bardiya - Rawal, Sunil (Patan Prospective Journal, 2022)
The essay explores the relationship between Land Tenure Practice and Food Security at Bardiya. “Tenure” is a social construct that specifies the ties between persons and groups of individuals through which rights and obligations regarding land management and usage are established. It is commonly characterized as a “bundle of rights”—specific rights to do particular activities with land or property. Food security is the ability of all people, at all times, to have access to sufficient, safe and nutritious food to meet their dietary needs and food preferences for an active and healthy life. The study's overarching goal is to determine the impact of land tenure practices on food security. The Secondary sources are the key for analyzing research. A Chi-square test was done on two category variables to see if there was a connection between land tenure and food security. According to the statistics, the variables Kitchen garden and Own agricultural land; Farm Categories and Food Consumed are associated. The p-value (.000) is found in the same row's "Asymptotic Significance (2-sided)" column. If this number is equal to or less than the requisite alpha level, the outcome is remarkable (normally .025). The findings indicate that there is a relationship between land tenure and food security.